EVALUASI EFEKTIVITAS IMPLEMENTASIEKONOMI LINGKUNGAN BERBASIS SDGs DALAMMENINGKATKAN KESEJAHTERAANMASYARAKAT DAN PENGHEMATAN SUMBERDAYA ALAM DI INDONESIA - Deddy Ahmad Fajar; Farah Nur Fauziah; Dewa Aray Dwiyanto Aray Dwiyanto (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2023)
This research aims to evaluate the effectiveness of implementationenvironmental economics based on Sustainable Development Goals (SDGs) inIndonesia in improving people's welfare and savingnatural resources. By focusing on gap analysis between objectivesexpected and the reality that occurs, this research uses the methodqualitative with a descriptive approach. Data is collected through observation,interviews, and documentation to understand the implementation of SDGs effectivelycomprehensive. The research results show that the implementation of the SDGs has been achievedmake a positive contribution in improving community welfareand saving natural resources in Indonesia. Programs thatfocused on developing local economy, agriculture, infrastructureenvironment, as well as proven savings in energy, water and raw materialseffective. Inter-sector coordination, community participation and collectionAccurate data is the key to success in implementing SDGs.The implication of this research is the need to develop more effective strategies for managing natural resources sustainably.Policy recommendations include improving coordination between sectors,strengthening community participation, and using innovative technology.Thus, the implementation of SDGs-based environmental economics can be achievedbecome the basis for improving community welfare and maintainingsustainability of natural resources in Indonesia. In conclusion, evaluatethe effectiveness of implementing SDGs-based environmental economics isan important step in achieving sustainable development goals.It requires joint efforts from the government, society and various sectorsstakeholders to ensure successful implementation andsustainable.